Angleška različica zgodovinske monografije o Tonetu Kralju – prevajalska refleksija - Biščak, Breda (Hieronymus, 2025)
The article sheds light on the process of translation of the historical monograph on Tone Kralj’s church paintings along the former Rapallo border written by the renowned Slovene historian, Prof Egon Pelikan. Four years and a half after the commencement of the translation process, which involved several revisions, the English version was finally published by the internationally acclaimed academic publishing house, Peter Lang. The reflection of the long and complicated translation process is based on the survey of e-correspondence with the author and on the comparison of various versions of the original and translation. The reflection involves not only linguistic and content-related aspects of translation of a humanities text from Slovene into English, but also the presentation of institutional factors that had an impact on the translation process, the quality of translation, and the life of the translator.